Aniconism: definitions, examples and comparative perspectives - Gaifman, Milette (Religion, 2017)
This introductory essay to this thematic issue on aniconism argues for the value of considering various forms of aniconism side by side. It summarizes briefly the historiography of the terms ‘aniconism’ and ‘aniconic,’ noting that they originate in the work of Johannes Adolph Overbeck, who coined the expressions anikonisch and Anikonismus. It considers current definitions and proposes ‘aniconism’ be used to denote divine presence without a figural image in religious practice, in the visual arts, and in visual culture more broadly. It then discusses three instances of aniconism from Greek antiquity: the cult of Aphrodite in Paphos, the pillar of Zeus depicted on a 4th-century BCE vase, and the seats of Zeus and Hekate on the island of Chalke. These examples illustrate some of the challenges that face the student of aniconism, particularly the difficulty in assessing the nature of an aniconic monument. The discussion then turns to the manner in which the terms are deployed and understood today. It notes the strong association between aniconism and the earliest phases of a particular visual tradition, the view of aniconism as a lesser mode of denoting divine presence, and the perception that aniconic worship is connected with an increased spirituality. Finally, the article highlights some of the common themes that emerge from the contributions to this thematic issue, including the need to consider various forms of aniconism and to expand the range of phenomena that can be regarded as aniconic.